Management of World Biosphere Reserves in Vietnam: Case Study at Cu Lao Cham - Hoi An Biosphere Reserve - Quang Hoc, Truong; Ngoc Thao, Le; Thi Ngoc Ha, Hoang (VNU Journal of Science: Policy and Management Studies; Vol 40 No 1DO - 10.25073/2588-1116/vnupam.4464, 2024)
By 2024, Vietnam has 11 Biosphere Reserves recognized by UNESCO, ranking second in Southeast Asia in terms of the number of Biosphere Reserves. However, the reception and utilization of the Biosphere Reserve designation in provinces and at the national level remain passive. In addition to maintaining annual commemorative activities and developing 10-year periodic reports, key activities to fulfill the three basic functions of Biosphere Reserves, namely Conservation, Support, and Development—have not been adequately pursued by localities. The 10-year periodic assessment reports required by UNESCO are fairly well-implemented by Biosphere Reserves and localities. However, the recommendations from these reports have not been clearly proposed to promote strengths and limit weaknesses in the sustainable development of future Biosphere Reserves. The underlying cause of these limitations is that the evaluation of the effectiveness of management and coordination of Biosphere Reserves from national to local levels still adheres to administrative trends, and the scientific evidence supporting the evaluation process is not sufficiently clear. Therefore, recommendations from periodic reports still tend to be procedural and responsible for the Vietnamese government agencies as well as UNESCO. Particularly, these recommendations have not been legally institutionalized or institutionalized to leverage the Biosphere Reserve title in the comprehensive and sustainable development of localities with Biosphere Reserves. Based on this reality, the construction of a Framework to evaluate the effectiveness of management and coordination of Vietnam's Biosphere Reserves through 6 management contents including i) Context and current management status; ii) Development of a Management Plan for each Biosphere Reserve; iii) Mobilization of input resources for management; iv) Management process and coordination mechanism; v) Output products of the management process; and vi) Results/Impacts of the management process. Within these six basic contents, 22 corresponding indicators and 65 specific indicators have been developed to accurately describe the context, conditions, reception process, and management/coordination/operation of each Biosphere Reserve with the participation of government authorities, scientists, business forces, local communities, and stakeholders. Thus, the application of the Framework for effective management evaluation for Vietnam's Biosphere Reserves in the process of building mid-term 5-year and periodic 10-year reports as well as the operation process and leveraging the Biosphere Reserve status of localities and countries, will help provide an accurate and objective description of the landscape of Vietnam's 11 Biosphere Reserves.